Control of Sindbis Virus Infection by Antibody in Interferon-Deficient Mice - Byrnes, Andrew P. (American Society for Microbiology, 2000)
Antibodies clear Sindbis virus from infected animals through an unknown mechanism. To determine whether interferon-induced pathways are required for this clearance, we examined mice which are unable to respond to alpha/beta interferon or gamma interferon. Although extremely susceptible to infection, such mice survived and completely cleared virus if antibodies against Sindbis virus were given.